Prenatal Diagnosis of Craniorachischisis Totalis Following an Initially Normal First-Trimester Ultrasound in a Woman With Two Previous Caesarean Births: A Case Report - Julius Mugisha; Stuart Turanzomwe; Ssewanyana Ernest; Charles Lugaaju; Esther C. Atukunda; Mugyenyi R. Godfrey (Cureus, 2026)
Craniorachischisis totalis is the most severe form of open neural tube defect and combines acrania/anencephaly with extensive open spinal dysraphism. It is rare, lethal, and usually identifiable prenatally, but diagnostic labeling may evolve across pregnancy as imaging findings become clearer. We report the case of a 33-year-old multiparous woman, gravida 4 para 2+1, with two previous caesarean births, whose booking ultrasound at 8 weeks and 4 days of amenorrhea showed a single live intrauterine embryo with no documented structural abnormality. She later underwent targeted fetal anomaly scanning at 21 weeks, which revealed absence of the calvarium and parenchymal tissue above the orbits, with findings interpreted as anencephaly. A repeat assessment confirmed anencephaly with spina bifida. After multidisciplinary counselling and because of the combination of a lethal fetal anomaly and two prior caesarean scars, termination was done by hysterotomy at 25 weeks of gestational age. The woman delivered a male fetus weighing 659 grams with Apgar scores of 1 and 0 at 1 and 5 minutes, respectively; operative documentation described anencephaly with an open spine and spina bifida, findings most consistent with craniorachischisis. The mother had an uncomplicated postoperative course and remained clinically well at follow-up. This case illustrates the evolution from an initially normal early pregnancy scan to a later lethal neural tube defect diagnosis, and it highlights the need for timely and targeted anomaly screening in resource-limited settings, careful phenotypic documentation, multidisciplinary counselling, and strong recurrence prevention advice after an affected pregnancy
Keywords: : anencephaly; craniorachischisis; neural tube defect; prenatal diagnosis; spina bifida